A DEAD-Box Helicase Mediates an RNA Structural Transition in the HIV-1 Rev Response Element. Issue 5 (10th March 2017) - Hammond, John A.; Lamichhane, Rajan; Millar, David P.; Williamson, James R.
Abstract: Nuclear export of partially spliced or unspliced HIV-1 RNA transcripts requires binding of the viral protein regulator of expression of virion (Rev) to the Rev response element (RRE) and subsequent oligomerization in a cooperative manner. Cellular DEAD-box helicase DEAD-box protein 1 (DDX1) plays a role in HIV replication, interacting with and affecting Rev-containing HIV transcripts in vivo, interacting directly with the RRE and Rev in vitro, and promoting Rev oligomerization in vitro . Binding of DDX1 results in enhancement of Rev oligomerization on the RRE that is correlated with an RNA structural change within the RRE that persists even after dissociation of DDX1. Furthermore, this structural transition is likely located within the three-way junction of stem II of the RRE that is responsible for initial Rev binding. This discovery of the stem II structural transition leads to a model wherein DDX1 can act as an RNA chaperone, folding stem IIB into a proper Rev binding conformation. Graphical Abstract: Highlights: DDX1 has been shown to increase the oligomerization of HIV-1 Rev on the cognate RNA RRE, although the mechanism is unclear. DDX1-associated Rev oligomerization enhancement correlates strongly with an RNA structural transition. This RNA structural transition is DDX1-mediated and persists even after DDX1 dissociation. Chemical probing experiments indicate that Rev and DDX1 binding effects overlap in the RRE RNA within the high affinity binding site stem II.